The obese inflammatory microenvironment may promote breast DCIS progression - Habanjar, Ola; Nehme, Rawan; Goncalves-Mendes, Nicolas; Cueff, Gwendal; Blavignac, Christelle; Aoun, Jessy; Decombat, Caroline; Auxenfans, Céline; Diab-Assaf, Mona; Caldefie-Chézet, Florence; Delort, Laetitia (Frontiers in Immunology, 2024)
Introduction Ductal carcinoma in situ (DCIS), characterized by a proliferation of neoplastic cells confined within the mammary ducts, is distinctly isolated from the surrounding stroma by an almost uninterrupted layer of myoepithelial cells (MECs) and by the basement membrane. Heightened interactions within the adipose microenvironment, particularly in obese patients, may play a key role in the transition from DCIS to invasive ductal carcinoma (IDC), which is attracting growing interest in scientific research. Adipose tissue undergoes metabolic changes in obesity, impacting adipokine secretion and promoting chronic inflammation. This study aimed to assess the interactions between DCIS, including in situ cancer cells and MECs, and the various components of its inflammatory adipose microenvironment (adipocytes and macrophages). Methods To this end, a 3D co-culture model was developed using bicellular bi-fluorescent DCIS-like tumoroids, adipose cells, and macrophages to investigate the influence of the inflammatory adipose microenvironment on DCIS progression. Results The 3D co-culture model demonstrated an inhibition of the expression of genes involved in apoptosis (BAX, BAG1, BCL2, CASP3, CASP8, and CASP9), and an increase in genes related to cell survival (TP53, JUN, and TGFB1), inflammation (TNF-α, PTGS2, IL-6R), invasion and metastasis (TIMP1 and MMP-9) in cancer cells of the tumoroids under inflammatory conditions versus a non-inflammatory microenvironment. On the contrary, it confirmed the compromised functionality of MECs, resulting in the loss of their protective effects against cancer cells. Adipocytes from obese women showed a significant increase in the expression of all studied myofibroblast-associated genes (myoCAFs), such as FAP and α-SMA. In contrast, adipocytes from normal-weight women expressed markers of inflammatory fibroblast phenotypes (iCAF) characterized by a significant increase in the expression of LIF and inflammatory cytokines such as TNF-α, IL-1β, IL-8, and CXCL-10. These changes also influenced macrophage polarization, leading to a pro-inflammatory M1 phenotype. In contrast, myoCAF-associated adipocytes, and the cancer-promoting microenvironment polarized macrophages towards an M2 phenotype, characterized by high CD163 receptor expression and IL-10 and TGF-β secretion. Discussion Reciprocal interactions between the tumoroid and its microenvironment, particularly in obesity, led to transcriptomic changes in adipocytes and macrophages, may participate in breast cancer progression while disrupting the integrity of the MEC layer. These results underlined the importance of adipose tissue in cancer progression.